Improving technology of bakery products when using additives - Z. A. Ivanova; F. K. Tkhazeplova (Новые технологии, 2018)
Creating bread technology using rice flour with the highest consumer qualities will increase the nutritional value of bread and expand the assortment of products. Rice flour protein, unlike wheat flour, does not have the ability to form and therefore creates some difficulties in the manufacture of bakery products. The studies examined the effects of the addition of rice flour in the amount of 10% to 50% of rice flour to wheat flour. Studies of the quality indicators of bread showed that with an increase in the amount of rice flour introduced, the quality of the manufactured products changed. The volume of bread, the structure of porosity and the quality of gluten become better when rice flour is added up to 10%. The quality of bread decreases with an increase in the amount of rice flour to 20%, namely the crumb becomes darker, tears and cracks appear. The results of the study have shown that the addition of sea buckthorn juice to the total mass of flour, and with the accumulation of acid 2.8 degrees / hour, the total acidity of the dough increases by 12.5%. This dose was applied in subsequent research papers. Laboratory baking with the addition to the dough of sea buckthorn juice in an amount of from 2.5 to 15% by weight of flour in the semi-finished product has been conducted. In the production of bread using rice flour, the addition of sea buckthorn juice to the semi-finished product at a dosage of 12.5% of the total weight of flour contributes to an improvement in the quality of the product. Thus, the specific volume of the finished product is increased by 7%, the porosity by 12% compared with the control option. The porosity is more uniform, the crumb bleaching effect was observed.